Polyalthia khaoyaiensis (Annonaceae), a new species from Thailand - Bunchalee, Pasakorn; Chantaranothai, Pranom; Johnson, David M.; Murray, Nancy A. (Phytotaxa, 2019)
A new species, Polyalthia khaoyaiensis, is proposed based on materials from central Thailand. The species appears most similar to Polyalthia meghalayensis and Polyalthia evecta, differing from these taxa in having shorter pedicels and usually two (rather than one) ovules per carpel. From P. meghalayensis it differs further in absence of a claw from the inner petals. The new species is described and illustrated. The conservation status of the species is considered and it is given an assessment of Least Concern (LC), as it is locally common in the hill evergreen forest of Khao Yai National Park.